2016
DOI: 10.1186/s12911-016-0321-4
|View full text |Cite
|
Sign up to set email alerts
|

The effect of an interactive weekly mobile phone messaging on retention in prevention of mother to child transmission (PMTCT) of HIV program: study protocol for a randomized controlled trial (WELTEL PMTCT)

Abstract: BackgroundImproving retention in prevention of mother to child transmission (PMTCT) of HIV programs is critical to optimize maternal and infant health outcomes, especially now that lifelong treatment is immediate regardless of CD4 cell count). The WelTel strategy of using weekly short message service (SMS) to engage patients in care in Kenya, where mobile coverage even in poor areas is widespread has been shown to improve adherence to antiretroviral therapy (ART) and viral load suppression among those on ART. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 13 publications
0
30
0
1
Order By: Relevance
“…This is a cross-sectional study of pregnant women living with HIV and enrolled in the WelTel PMTCT trial from June 2015 to July 2016. The WelTel PMTCT trial is a multicentre randomised controlled trial designed to test the efficacy of weekly interactive mobile text messages for improving retention in PMTCT care among women and infants in western Kenya [28]. Pregnant women living with HIV, 18 years or older, consecutively presenting for their first antenatal care (ANC) visit in their current pregnancy were informed about the WelTel PMTCT trial by a trained local research assistant at their clinic.…”
Section: Study Design Population and Locationmentioning
confidence: 99%
“…This is a cross-sectional study of pregnant women living with HIV and enrolled in the WelTel PMTCT trial from June 2015 to July 2016. The WelTel PMTCT trial is a multicentre randomised controlled trial designed to test the efficacy of weekly interactive mobile text messages for improving retention in PMTCT care among women and infants in western Kenya [28]. Pregnant women living with HIV, 18 years or older, consecutively presenting for their first antenatal care (ANC) visit in their current pregnancy were informed about the WelTel PMTCT trial by a trained local research assistant at their clinic.…”
Section: Study Design Population and Locationmentioning
confidence: 99%
“…In this study, participants will receive an interactive weekly SMS and based on the response by the participant, a PMTCT nurse will be prompted to follow-up on any indications of problems. The primary outcome will be infant retention in care by quantifying the number of infants testing for HIV at 24 months from delivery (Awiti et al, 2016). The most recent protocol is a randomized pilot trial, taking place in South Africa, which evaluates the feasibility of a conducting a larger pilot study that will assess the effectiveness of an interactive weekly text message plus motivational interviews to improve adherence to breastfeeding by HIV-infected women.…”
Section: Ongoing Studiesmentioning
confidence: 99%
“…In addition, studies addressing structural factors showed promising results with integration of postpartum care into routine care for the child or family [66] [67], mHealth reminders and cash transfers [68][69][70][71][72]. Ongoing studies will evaluate effects of mHealth strategies [73,74], reaching women with mental health challenges in pregnancy and postpartum [75,76] and adherence clubs/decentralized care [77]. Women in different contexts will require different types of support [78,79] and an adaptive trial design [80] may be an efficient way to evaluate strategies to combine intervention elements to support women to remain in care [81].…”
Section: Discussionmentioning
confidence: 99%